2008
DOI: 10.1002/app.27897
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of polylactide after repeated cleanings

Abstract: The ability of polylactide (PLA) to retain its mechanical properties after repeated cleanings at various pH levels, washing temperatures, and drying conditions has been studied. One of the problems with PLA is its poor resistance to hydrolysis, especially under alkaline conditions. In this study, PLA fabrics were sent through 50 cleaning cycles with different pH levels (8 or 10), washing temperatures (35 or 558C), and drying conditions (air dry at 218C/65% relative humidity or tumble dry at 50 or 708C). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In Run b8 to Run b9 of S 1 , and in Run c2 to Run c9 of S 2 , NH 4 Cl was added into the reactors to evaluate the promotion effect of ammonia on PLA degradation under hyperthermophilic condition. S 1 was operated without pH control while pH in S 2 was maintained at 7.5 by automatic titration of 10 N KOH in Run c2 to Run c9 to promote the PLA degradation as pH drops by degradation of PLA to lactic acid, and it was indicated that higher pH of aqueous solution was favorable for the PLA hydrolysis (Karst et al, 2008;Tsuji and Ikarashi, 2004).…”
Section: Reactor Configuration and Operationmentioning
confidence: 99%
“…In Run b8 to Run b9 of S 1 , and in Run c2 to Run c9 of S 2 , NH 4 Cl was added into the reactors to evaluate the promotion effect of ammonia on PLA degradation under hyperthermophilic condition. S 1 was operated without pH control while pH in S 2 was maintained at 7.5 by automatic titration of 10 N KOH in Run c2 to Run c9 to promote the PLA degradation as pH drops by degradation of PLA to lactic acid, and it was indicated that higher pH of aqueous solution was favorable for the PLA hydrolysis (Karst et al, 2008;Tsuji and Ikarashi, 2004).…”
Section: Reactor Configuration and Operationmentioning
confidence: 99%
“…It has also been found that high temperature, long time and pH levels of dyeing result in fiber strength and elongation losses. 18,25 Phillips et al have found that the molecular weight of PLA exhibited a significant reduction of 15% and 65% after dyeing at 110 and 120 C for 30 min at pH 5, respectively. 11…”
Section: Dye Exhaustion In Pla Dyeingmentioning
confidence: 98%
“…Yang et al [61] studied the effect of the pH (8 or 10) and water temperature (35 or 55°C) during washing and the effect of drying conditions (air dry at 21°C/65% relative humidity or tumble dry at 50 or 70°C) on the ability of PLA to retain its mechanical properties after repeated laundering (50 cleaning cycles). It is recommended [61] that PLA fabrics should be cleaned with detergents with a low pH (i.e., pH 8), and detergents with a high pH (i.e., pH 10) should be avoided because they result in lower breaking tenacity, breaking elongation, and modulus retention due to the possible hydrolysis of the PLA polymer under strongly alkaline conditions. It is reported that washing PLA fabric at a water temperature of 35°C and air drying it at 21°C 65% RH resulted in higher modulus retention than washing and drying at higher temperatures [61].…”
Section: Washing and Dryingmentioning
confidence: 99%
“…It is recommended [61] that PLA fabrics should be cleaned with detergents with a low pH (i.e., pH 8), and detergents with a high pH (i.e., pH 10) should be avoided because they result in lower breaking tenacity, breaking elongation, and modulus retention due to the possible hydrolysis of the PLA polymer under strongly alkaline conditions. It is reported that washing PLA fabric at a water temperature of 35°C and air drying it at 21°C 65% RH resulted in higher modulus retention than washing and drying at higher temperatures [61]. Hydrolysis of PLA polymer was stated to be the main cause of loss in mechanical properties.…”
Section: Washing and Dryingmentioning
confidence: 99%
See 1 more Smart Citation